Zinner’s Syndrome: A Rare Diagnosis of Dysuria Based on Imaging - Ahmed Ibrahimi; Abdelmoughit Hosni; Idriss Ziani; Fatima Zahra Laamrani; Hachem El Sayegh; Laila Jroundi; Lounis Benslimane; Yassine Nouini (Case Reports in Urology)
Zinner’s syndrome is a rare congenital malformation of the seminal vesicle and ipsilateral upper urinary tract, due to developmental arrest in early embryogenesis of the Müllerian duct. Clinical presentation is nonspecific and includes voiding symptoms such as dysuria, ejaculatory disorders, and hypogastric or perineal pain. The diagnosis is made with imaging techniques, notably Magnetic Resonance Imaging (MRI) which remains the gold standard exam for diagnosis confirmation and therapeutic management. Treatment options depend on the severity of symptoms, the size of the cyst, and the complications. Herein, we report a rare case of a 33-year-old young patient who presented recurrent dysuria and ejaculatory disorders for the last 5 years. Imaging studies revealed an empty left renal fossa, with cystic pelvic mass related to the seminal vesicle and which was compatible with the diagnosis of Zinner’s syndrome. The patient underwent successful laparoscopic removal of the cyst and seminal vesicle, with total disappearance of urinary and sexual complaints with a 3-year follow-up.